El plan de negocios y la viabilidad de un snack bar móvil de eventos sociales - Sánchez Pacheco, Lidia Carolina (2025)
The identified problem lies in the limited innovation and differentiation of gastronomic offerings in social events, creating opportunities for mobile proposals with added value. The objective of the study was to design a business plan for a Mobile Snack Bar, incorporating strategic analysis (SWOT, IFE/EFE matrices, PESTEL, and Porter’s five forces), value proposition, marketing strategy, organizational structure, and financial projections, as well as determining its technical, legal, and financial feasibility. A quantitative approach was applied, using surveys to understand perceptions, preferences, and willingness to pay among potential clients, thus supporting the design of the proposal..............